The Nordic Model and Management in International Corporations:A Scoping Review - Berg, Tone Elisabeth; Eggen Børve, Hege; Mørk Røkenes, Fredrik (Nordic Journal of Working Life Studies, 2023)
The overall aim of this scoping review is to present empirical studies regarding how the Nordic model has been investigated in relation to management in international companies. The subse quent objective is to discuss the model’s robustness regarding internationalization. The question raised is how the Nordic model, in relation to management, is configured in empirical studies undertaken in international corporations. Using systematic literature searches to examine peer- reviewed articles published between 2000 and 2022, 15 out of 972 studies were eligible for a full review. Primarily, one facet of the model was investigated: workplace democracy. Foreign-owned companies operating in Nordic countries partly adopted the model, whereas the model was implemented to some extent in Nordic-owned companies abroad. Management’s support and employee involvement were considered important. This review indicates that there is pressure on the model, although it has extended beyond the Nordic border and appears to be adaptable to global working life.